The impact of the "COVID-19 life" on the Tokyo metropolitan area households with primary school-aged children: A study based on spatial characteristics - Shun Tomikawa; Yukari Niwa; Hwajin Lim; Maiko Kida (Journal of Urban Management, 2021)
This study aims to elucidate the effects that staying home due to COVID-19 has had on households with primary school-age children living in the central area. To determine the differences in states of mind between people in the central area and people in other areas, we investigated the changes in their "daily lives" including matters related to school; playing outside; associating with other children; "communication" including communication with family and friends; and the "use of information technologies" that secure communication. Moreover, we explored households that are satisfied even when they are unable to go out and clarified how children and their parents who live in the central area perceive the current situation. The study results indicate that the risks of COVID-19 in large cities have spatial characteristics and increase the burden on households raising children. Particularly in the central area, which has a high population density, the changes children experience are striking. Furthermore, due to the inadequate amount of open space, a strong awareness of the "new normal (avoiding the "Three Cs" (closed spaces, crowded places, and close-contact settings)" is required.
Keywords: 710; COVID-19; Tokyo metropolitan area; Primary school children; Questionnaire survey; Text mining analysis